La croûte océanique de l'île de la Désirade - Bertrand, Hervé; Dromart, Gilles; Guillot, Stéphane; Lardeaux, Jean-Marc; Nicollet, Christian; Thomas, Pierre (Planet Terre, 2001)
Description de la croûte océanique de la Désirade, hypothèse sur son origine.